Getting at Mode Share: Comparing 3 Methods of Travel Mode Measurement for School Travel Research. (18th March 2019) - Sersli, Stephanie; Rothman, Linda; Winters, Meghan
ABSTRACT: BACKGROUND: Mode share is an important metric for active school travel programs. Common methods for measuring mode share include Hands Up surveys and family surveys, but these require teacher and parental involvement. We used these methods as part of an evaluation of a school‐based bicycle training program, and added a novel observational count approach. This paper compares mode share results across the 3 methods. METHODS: We collected data over 2015–2017 at 16 elementary schools. Our outcome of interest was mode share (walk, drive, and bicycle). RESULTS: We found variations in travel mode estimates between methods and across schools. Overall most school journeys were made by walking (55.7% by observational counts, 46.3% by Hands Up surveys, and 51.5% by family surveys) or car (42.5%, 51.4%, and 46.2%, respectively), and a small proportion by bicycle (1.8%, 2.3%, and 2.2%, respectively). At individual schools, Hands Up and family survey results were similar; there was less agreement between these and observational counts. CONCLUSION: School travel practitioners face pragmatic choices in data collection. Observational counts are a nonintrusive method suited for school‐wide travel patterns. Hands up and family surveys may be more appropriate for assessing differences between classrooms, ages, or family characteristics.